Case report: Tongue metastasis as an initial sign of clear cell renal cell carcinoma and its prognosis - Liu, Shuo; Liu, Hongyun; Weng, Bowen; Hou, Sichuan (Frontiers in Oncology, 2025)
Clear cell renal cell carcinoma (ccRCC) is the most prevalent and lethal subtype of renal cell carcinoma (RCC), characterized by a poor prognosis and a high likelihood of distant metastasis. Nonetheless, metastasis of ccRCC to the tongue remains rare. Diagnosing and planning treatment for patients who initially present with tongue metastasis can be particularly challenging, as few cases have been reported in the literature. We present a case of a 62-year-old man who presented with a painful lump on the right anterior border of his tongue. Histological examination revealed lobulated and nested epithelial cell clusters with moderate dysplasia and frequent mitotic figures within the lamina propria. Immunohistochemistry showed positivity for vimentin, CD10, PAX-8, and epithelial membrane antigen (EMA), but negativity for PAX-2, calponin, S-100 protein, periodic acid-Schiff with diastase (PAS-D), P63, P40, and CK7, confirming the diagnosis of ccRCC metastasis to the tongue. After comprehensive evaluation and multidisciplinary team consultation, the patient underwent cytoreductive nephrectomy (CN), metastasectomy, and targeted therapy. According to the Response Evaluation Criteria in Solid Tumors (RECIST) Version 1.1, the patient maintained stable disease (SD) during systemic treatment. Unfortunately, treatment was discontinued due to adverse drug reactions, and the patient was transitioned to palliative care. His disease progressed to progressive disease (PD), and he ultimately succumbed to systemic infection, with a progression-free survival (PFS) of approximately 15 months. This case highlights the urgent need for improved therapeutic strategies to manage symptoms and prolong survival in patients with this rare metastatic presentation.